Effects of Violence on Adherence to Antiretroviral Therapy: - Virginia, Thonyiwa (Amref International University, 2025)
Background: Adolescents living with HIV (ALWHIV) face significant challenges to maintain ART adherence compared to other age groups in sub–Saharan Africa where HIV prevalence and violence are both high. In Malawi, evidence remains limited on how different forms of violence affect ART adherence among ALWHIV Methodology: A cross-sectional mixed-methods study conducted in April 2025 among 190 ALWHIV aged 10–19 attending ART teen clubs in area 25, Baylor and Mtenthera health facilities in Lilongwe Malawi. Participants were selected through simple random sampling. Quantitative data were collected using Kobo Toolbox and analysed in SPSS v22. Chi-square test was used for bivariate analysis and multivariate logistic regression assessed associations between ART adherence and physical, emotional and sexual violence. Qualitative data from two focus group discussions and six key informant interviews were analysed thematically using NVivo. Results: Among respondents, 56.3% (n=107) were females, only 54% attained optimal adherence, and 78% achieved viral suppression. Prevalence of emotional, sexual, and physical violence was 76.8%, 53%, and 30.5% respectively. Chi-square bivariate analysis showed associations between all types of violence and adherence were statistically significant (p<0.05). Multivariate logistic regression revealed that emotional violence was associated with 60% lower odds of adherence (OR = 0.40; 95% CI: 0.21–0.78; p < 0.01), and physical violence with 58.8% reduced odds (OR = 0.412; 95% CI: 0.20–0.87; p = 0.019). Missed clinic visits showed a negative trend but were not statistically significant. Qualitative data echoed these findings, linking violence to low self-esteem and poor adherence behavior. Adolescents were reluctant to report violence. Conclusion: Emotional and physical violence are significantly associated with suboptimal ART adherence leading to high viral loads among ALWHIV. Routine screening for violence and enhanced clinical monitoring are recommended to improve ART outcomes and support progress towards HIV epidemic control.
The Case of Adolescents Living with HIV in Lilongwe, Malawi
A research thesis submitted to the Department of Community Health, School of Public Health in partial fulfilment of the requirements for the award of Master of Public Health (epidemiology) of Amref International University